Analysis of Factors Affecting Consumer Decision-Making in Choosing Online Food Delivery in Indonesia - Elysia Elverda; Tasliyah Athaya Nahdah; Sambudi Hamali (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: Online Food Delivery (OFD) services increased after the COVID-19 pandemic. However, post-pandemic repurchase intentions on Indonesian OFD platforms such as GoFood, GrabFood, and ShopeeFood have declined. To understand the success factors for OFD service acceptance, this study employed a modified Technology Acceptance Model (TAM) approach. Purpose: This study aimed to determine the factors influencing repurchase intention, namely perceived price, perceived usefulness, perceived ease of use, and service quality mediated by trust and consumer satisfaction among OFD platform consumers in Indonesia. Method: The study employed a quantitative approach to investigate the causal relationships between variables. A questionnaire was distributed to 724 online food delivery (OFD) consumers in several big cities of Indonesia, including Jabodetabek, Bandung, Surabaya, Medan, Makassar, Balikpapan, and Yogyakarta. Respondents were selected using quota sampling. Structural equation modeling was used to test the research hypotheses and empirically investigate the factors influencing repurchase intention mediated by consumer satisfaction and trust among OFD platform consumers in Indonesia. Findings: This study revealed that perceived price, perceived usefulness, ease of use, service quality, customer satisfaction, and trust influence repurchase intention. Among these factors, perceived usefulness is the most significant predictor of customer repurchase intention. In addition, trust mediates perceived price and repurchase intention, while customer satisfaction mediates the relationship between perceived usefulness, ease of use, service quality, and repurchase intention. Conclusions: These findings suggest that post-COVID-19, by understanding the factors that influence repurchase intention (perceived price, perceived usefulness, ease of use, service quality, trust, and customer satisfaction), OFDs can increase their sales. Research implication: The desire to repurchase through OFDs can be achieved through affordable product prices, having a communication plan that makes customers feel valued when using the website, implementing advertising strategies to make the website easy to use, fast and quality responses, and attractive visual features and designs.